Mupirocin prophylaxis against nosocomial Staphylococcus aureus infections in nonsurgical patients: a randomized study. - Wertheim, H; Vos, M; Ott, A; Voss, A; Kluytmans, J; Vandenbroucke-Grauls, C; Meester, M; van Keulen, P; Verbrugh, H (2004)
BACKGROUND: Staphylococcus aureus nasal carriage is a major risk factor for nosocomial S. aureus infection. Studies show that intranasal mupirocin can prevent nosocomial surgical site infections. No data are available on the efficacy of mupirocin in nonsurgical patients. OBJECTIVE: To assess the efficacy of mupirocin prophylaxis in preventing nosocomial S. aureus infections in nonsurgical patients. DESIGN: Randomized, double-blind, placebo-controlled trial. SETTING: 3 tertiary care academic hospitals and 1 nonacademic hospital. PATIENTS: 1602 culture-proven S. aureus carriers hospitalized in nonsurgical departments. INTERVENTION: Therapy with mupirocin 2% nasal ointment (n = 793) or placebo ointment (n = 809), twice daily for 5 days, started 1 to 3 days after admission. MEASUREMENTS: Nosocomial S. aureus infections according to defined criteria, in-hospital mortality, duration of hospitalization, and time to nosocomial S. aureus infection. Staphylococcus aureus isolates were genotyped to assess whether infection was caused by endogenous strains. RESULTS: The mupirocin and placebo groups did not statistically differ in the rates of nosocomial S. aureus infections (mupirocin, 2.6%; placebo, 2.8%; risk difference, 0.2 percentage point [95% CI, -1.5 to 1.9 percentage points]), mortality (mupirocin, 3.0%; placebo, 2.8%; risk difference, -0.2 percentage point [CI, -1.9 to 1.5 percentage points]), or duration of hospitalization (median for both, 8 days). However, time to nosocomial S. aureus infection was decreased in the mupirocin group from 12 to 25 days (P > 0.2). A total of 77% of S. aureus nosocomial infections were endogenous. LIMITATIONS: A few infections in both groups may have been missed because investigators assessed a patient for infection only if microbiology culture results were positive for S. aureus. CONCLUSION: Routine culture for S. aureus nasal carriage at admission and subsequent mupirocin application does not provide effective prophylaxis against nosocomial S. aureus infections in nonsurgical patients.